Emprego do ultrassom para a desemulsificação de petróleos provenientes do pré-sal - Gatiboni, Thaís Lavarda (2020)
The presence of emulsified water in crude oil is a natural consequence of the formation and the production process, leading to crude oil emulsions in petroleum production. Emulsion separation is necessary for industrial treatment and characterization, resulting in an oil phase with minimum levels of water, salt, and sediments. This separation not only avoids problems in the industrial refining process and in the finished products but also enables accurate crude oil characterization, which is linked directly to the crude oil market price. In this work, the use of ultrasound systems was evaluated, both direct and indirect application, for the development of a laboratory method for removing water from natural water-in-oil emulsions. Three medium crude oils, from Pre-salt and Post-salt fields, with different water content (2.99, 8.23, and 78.3%), were evaluated. Initially, exploratory conditions were used based on previous works in the literature for heavy and extra heavy crude oils. Main conditions were evaluated in a 2³ factorial design: time, temperature, and ultrasound amplitude. After investigating different ultrasound probes and reactors, in the presence of a chemical demulsifier, a condition for emulsion separation was achieved. The optimization of the process was done through a central composite design, which evaluated the concentration of the demulsifier, the time, the temperature, and the amplitude of ultrasound. The best separation efficiency was obtained with 20 min of ultrasound application, 55 °C, 50% ultrasound amplitude, and demulsifier concentration of 30 mg L-¹. From this condition, additional evaluations with longer ultrasound application time and using systems with indirect ultrasound application (baths) were performed. The evaluation of a system without the use of ultrasound was also carried out, under the conditions already optimized for the method with ultrasound. Using the process conditions optimized for each crude oil, demulsification efficiencies were 53, 74 and, 66% for crude oils with initial water contents of 2.99, 8.23, and 78.3%, respectively. After the demulsification process, the crude oils were characterized for density, °API, dynamic and kinematic viscosity, total acid number, salt content, sediments, and concentration of metals, S and N.